2022
DOI: 10.34172/joddd.2022.040
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of bleaching agents on lithium disilicate glass ceramics

Abstract: Background. Aesthetic expectations have increased the use of aesthetic materials in dentistry. Lithium disilicates are frequently used materials for these expectations. Bleaching is another method used to provide aesthetics. Bleaching processes on restorative materials are not fully known. This study investigated the effect of at-home and in-office bleaching methods on the color change, surface roughness, and topography of lithium disilicate glass-ceramic materials produced with two different techniques and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Previous studies [49,51] had reported that the application time is signi cant in the effect of BLE on ceramics. Similar to this study, the number of studies in which glazed and mechanically polished ceramics were examined together is insu cient, and studies [21,23,47,52] found that glazed surfaces were less affected than mechanically polished surfaces in parallel with this study. The researchers reported that the magnitude of the effect of BLE is related to the application time.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies [49,51] had reported that the application time is signi cant in the effect of BLE on ceramics. Similar to this study, the number of studies in which glazed and mechanically polished ceramics were examined together is insu cient, and studies [21,23,47,52] found that glazed surfaces were less affected than mechanically polished surfaces in parallel with this study. The researchers reported that the magnitude of the effect of BLE is related to the application time.…”
Section: Discussionsupporting
confidence: 70%
“…There is no study on the effect of beverage with Sambucus Nigra on the color of CAD-CAM ceramic or hybrid ceramic materials. There are several studies [7,15,[21][22][23] examining the effect of polishing methods, BLE or PDP on the color of CAD-CAM restorative materials, but no study has examined these variables together. For these reasons, the aim of this study was to evaluate the effect of energy beverage and immune-boosting beverage with Sambucus Nigra, in-o ce BLE with HPS and PDP on color of CAD-CAM FC, ZLS and HC.…”
Section: Introductionmentioning
confidence: 99%